BioRef: a versatile time-of-flight reflectometer for soft matter applications at Helmholtz-Zentrum Berlin - Strobl, Markus; Steitz, R.; Kreuzer, Martin; Rose, M.; Herrlich, H.; Mezei, F.; Grunze, Michael; Dahint, Reiner (Review of scientific instruments, 2011)
BioRef is a versatile novel time-of-flight reflectometer featuring a sample environment for in situ infrared spectroscopy at the reactor neutron source BER II of the Helmholtz Zentrum Berlin für Materialien und Energie (HZB). After two years of design and construction phase the instrument has recently undergone commissioning and is now available for specular and off-specular neutron reflectivity measurements. BioRef is especially dedicated to the investigation of soft matter systems and studies at the solid-liquid interface. Due to flexible resolution modes and variable addressable wavelength bands that allow for focusing onto a selected scattering vector range, BioRef enables a broad range of surface and interface investigations and even kinetic studies with subsecond time resolution. The instrumental settings can be tailored to the specific requirements of a wide range of applications. The performance is demonstrated by several reference measurements, and the unique option of in situ on-board infrared spectroscopy is illustrated by the example of a phase transition study in a lipid multilayer film.